2018
DOI: 10.1021/acs.inorgchem.8b01174
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Characterization of NaGaS2, A High Thermal Conductivity Mid-Infrared Nonlinear Optical Material for High-Power Laser Frequency Conversion

Abstract: Infrared nonlinear optical (IR NLO) crystals are the major materials to widen the output range of solid-state lasers to mid- or far-infrared regions. The IR NLO crystals used in the middle IR region are still inadequate for high-power laser applications because of deleterious thermal effects (lensing and expansion), low laser-induced damage threshold, and two-photon absorption. Herein, the unbiased global minimum search method was used for the first time to search for IR NLO optical materials and ultimately fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…[4] The lack of structural information on NaGaS2 (and NaGaSe2) might suggest a more or less deliberate omission of this compound due to it possessing no valuable properties; however, a recent report on its calculated structure and optical properties showed that this is not the case. [5] The calculations indicate that NaGaS2 has a 3D framework structure and a second harmonic generation response superior to that of AgGaS2. Intrigued by this unexpected missing link in the MGaS2 family and, moreover, one that is expected to exhibit important SHG behavior, we became interested in its synthesis in order to determine its structure and probe its physical properties.…”
mentioning
confidence: 93%
“…[4] The lack of structural information on NaGaS2 (and NaGaSe2) might suggest a more or less deliberate omission of this compound due to it possessing no valuable properties; however, a recent report on its calculated structure and optical properties showed that this is not the case. [5] The calculations indicate that NaGaS2 has a 3D framework structure and a second harmonic generation response superior to that of AgGaS2. Intrigued by this unexpected missing link in the MGaS2 family and, moreover, one that is expected to exhibit important SHG behavior, we became interested in its synthesis in order to determine its structure and probe its physical properties.…”
mentioning
confidence: 93%
“…There are plenty of successful cases in the discovery of novel materials using CSP . However, it is rarely used in DUV NLO materials due to their complex composition, large number of atoms in unit cell, and most importantly, the lack of guidelines to determine the compositions and proportions . Herein, guided by the fluorooxoborates strategy of tuning the BO 3 /BO 3 F ratio in layers, five stable structures with the composition of BaB 2 O 3 F 2 (I–V) are discovered using ab initio evolutionary algorithm USPEX .…”
Section: Figurementioning
confidence: 99%
“…4 KDP). [35][36][37] Herein, guided by the fluorooxoborates strategy of tuning the BO 3 /BO 3 Fratio in layers,f ive stable structures with the composition of BaB 2 O 3 F 2 (I-V) are discovered using Most importantly,t he influences of BO 3 :BO 3 F ratio and their number density on band gap,birefringence and SHG effects are investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al, 2017), light generation and modulation (J. Chen et al, 2018), optical parametric amplification (Kumbhakar and Kobayashi, 2007;Popov and Shalaev, 2006), laser frequency conversion (D. Hou et al, 2018a), modulators (Grote et al, 2002), and optical switches (Biswal et al, 2019;. In addition, nonlinear optics have remarkable applications in dynamic image processing (Van Steenwinckel et al, 2001), sensing (Ray, 2010), high resolution imaging (Miller et al, 2002), optical computing (Hutchinson and Milburn, 2004), optical fiber communication (Arivuoli, 2001), optical data storage (Iliopoulos et al, 2010), and materials analysis (Y. R. Shen, 1989).…”
Section: Introductionmentioning
confidence: 99%